Antimicrobial susceptibility and serotype distribution of Streptococcus pneumoniae and molecular characterization of multidrug-resistant serotype 19F, 6B, and 23F pneumococci in Northern Thailand - Watanabe H. (2014)
Penicillin-resistant Streptococcus pneumoniae is widely spread worldwide. Our study was undertaken to examine the susceptibility and serotypes of S. pneumoniae in northern Thailand. Ninety-three S. pneumoniae strains were isolated from 93 patients at Chiang Mai University Hospital, Chiang Mai, Thailand, from September 1999 to June 2000. The strains were isolated from sputum (n = 51), blood (n = 15), nasopharynges (n = 14), and other sources (e.g., pus, ears, ascites, and cerebrospinal fluid) (n = 13). Of the 93 isolates, 29 (31.2%) were susceptible, 24 (25.8%) showed intermediate resistance (MIC, 0.12 to 1.0 μg/ml), and 40 (43.0%) were fully resistant (MIC, ≥2.0 μg/ml) to penicillin G. Seven (46.7%) from blood, 5 (35.7%) from nasopharynges, 15 (29.4%) from sputum, and 2 (15.4%) from other sources were susceptible isolates. Serotyping with the use of antiserum revealed differences in the predominant types that were susceptible (6A, 11A, and 19A), intermediately resistant (6B and 23F), and fully resistant (6B, 19F, and 23F). Molecular typing by pulsed-field gel electrophoresis of multidrug-resistant pneumococci showed four patterns (A, B, C, and D) for 16 isolates of serotype 19F, with pattern B being predominant (12 isolates). This finding was different from that with the Taiwan multidrug-resistant serotype 19F clone. Eleven isolates of serotype 6B all showed pattern E, and nine isolates of serotype 23F showed two patterns (F and G), with pattern F being predominant (seven isolates). This finding was similar to that with the Spanish multidrug-resistant serotype 23F clone. Our results indicated that the resistance of pneumococci to antibiotics in northern Thailand is progressing rapidly and that effort should be intensified to prevent any spread of pandemic multidrug-resistant serotypes 19F, 6B, and 23F.